1989
DOI: 10.2343/geochemj.23.321
|View full text |Cite
|
Sign up to set email alerts
|

Anatexis and chemical evolution of pelitic rocks during metamorphism and migmatization in the Hidaka metamorphic belt, Hokkaido.

Abstract: The southernmost Hidaka metamorphic belt consists mainly of cordierite tonalite intrusions and pelitic metamorphic rocks ranging from the greenschist to the granulite facies. Anatectic migmatites are common in the higher amphibolite and granulite facies zones. Compositional changes in major, rare earth elements and some other trace metals are so small that they are undetectable among the pelitic metamorphic rocks of zones A + B + C and D, but they are large enough to be detected in the higher am phibolite (zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…1 2 55 Ma 3 , 1992;Toyoshima et al, 1994;Owada et al, 2003 55 Ma Rb-Sr Owada et al, 1991;, 1992 , 1984;Tagiri et al, 1989;Osanai et al, 1991Osanai et al, , 1992Owada et al, 1991;, 1992;Shimura et al, 1992Shimura et al, , 2004Komatsu et al, 1994;, 1994; Whitney and Evans 2010, 1986Fig. 1a -, 1986 , 1983 Kiyokawa, 1992, Ueda et al, 2001Komatsu et al, 1983 Komatsu et al (1986) and Shimura et al (2004).…”
Section: Kmmentioning
confidence: 99%
“…1 2 55 Ma 3 , 1992;Toyoshima et al, 1994;Owada et al, 2003 55 Ma Rb-Sr Owada et al, 1991;, 1992 , 1984;Tagiri et al, 1989;Osanai et al, 1991Osanai et al, , 1992Owada et al, 1991;, 1992;Shimura et al, 1992Shimura et al, , 2004Komatsu et al, 1994;, 1994; Whitney and Evans 2010, 1986Fig. 1a -, 1986 , 1983 Kiyokawa, 1992, Ueda et al, 2001Komatsu et al, 1983 Komatsu et al (1986) and Shimura et al (2004).…”
Section: Kmmentioning
confidence: 99%
“…subhorizontal crustal displacement (D2) by Komatsu et al (1989). The granitic rocks are almost S-type tonalites formed by anatexis in the deep crust (Tagiri et al 1989;Osanai et al, 1991;Shimura et al 1992), and intruded into the decollement and shear zones (Toyoshima 1991;Shimura 1992). Komatsu et al (1994) showed that granulite facies gneisses underwent decompression under increasing temperature conditions during the peak metamorphic and deformation stage (D,) and suggested that the unloading was caused by extensional doming due to intrusion and underplating of mafic magma.…”
mentioning
confidence: 99%
“…and Katsushima, 1986;, 1987Miyashita andYoshida, 1988, 1994;Miyashita and Watanabe, 1988;, 1990, 1994, 1992 , , 1985;Osanai et al, 1986Osanai et al, , 1991Osanai et al, , , 1997 Fig Amphibolites from the Main zone of Hidaka metamorphic belt are distributed in zones and b . In this study, central and southern areas of the Main Zone were studied and the southern area was subdivided into northern and southern parts.…”
mentioning
confidence: 99%
“…H2O , , 1982H2O , , , 1986H2O , , 1985H2O , , Osanai et al 1986H2O , , , 1991H2O , , 1986 3 Fig : schlieren structure composed of Opx tonalite and Opx amphibolite Zone in Nanashino-sawa river , e: agmatite structure of Opx amphibolite intruded by Opx tonalite Zone in Benikaru-zawa river , f: gneissose brown-Hbl amphibolite Zone in Ogawara-zawa river , g: thin Grt amphibolite layer within Opx amphibolite Zone in Sasshibichari river , h: banded green-Hbl amphibolite Zone in Nanashino-sawa river , i: dolerite intruding to shale Shimokawa area , j: pillow lava composed of Cpx-basalt Nupun-Tomuraushi river in Tomuraushi area , k: gneissose amphibolite Uchino-sawa river in Ochiai area l: boundary between greenschist and slate Kanano-sawa river in Ochiai area . Table 1 Table 2 Fig Table 2 SrI Nd NdI , 1984;Tagiri et al, 1989;, 1999 NdI , 1993;Kiminami et al, 1994;Watanabe and Iwata, 1987N-MORB Maeda and Kagami, 1996, 1990Maeda and Kagami, 1996; , …”
mentioning
confidence: 99%
See 1 more Smart Citation